EXPLORATION OF ASIA LEADERSHIP THEORY: LOOKING FOR AN ASIAN ROLE IN THE FIELD OF LEADERSHIP THEORY - C. Budi Santoso (Universitas Gadjah Mada, 2019)
This study begins with the question of whether Western leadership theory is universal and where is Asia's contribution to this theory of leadership. Studies show that the theory of Asian leadership is local and influenced by the cultural influences of Asian local communities. Harmony and stability are the essences of Asian local culture. The leadership process is voluntary, collectivity, and is in a traditional or informal social structure. The effectiveness of traditional leadership is more concerned with aspects of guarding and achieving an atmosphere of harmony and stability. Furthermore, Western leadership theory is built from an organizational perspective that is competing to gain resources and maintain the organization's life. The West leadership process is mechanical, formal and transactional. Leadership effectiveness is the ability to win the competition and defend itself in a strong position in the competition. The differences in the approaches to Asian and Western leadership theory are in line with the concept of low-context and high-context perspective. This is also in line with the contingency approach for effective leadership. The study states that the position of Asian and Western leadership theory is the same, both groups of theories are on a practical level that emphasizes contextual conformity. The globalization paradigm has strengthened Western